Percepções do fator acidentário de prevenção: o (in)sustentável meio ambiente do trabalho na pós-modernidade - Fortes, Vinícius Borges (My University, 2014)
The research approaches the perceptions of Accident Prevention Factor as a normative instrument for achieving sustainability in the environment of work. Seeking sustainability in terms of labor relations leads to ensuring a decent working environment for present and future generations of workers. Given this, the research achieves its objectives by exposing a historical-sociological analysis of the transition from working as biological-evolutionary training of human beings to the need for biological and social work, approaching the environment of work and the significant transformations of production processes. Moreover, research demonstrates the relevance of the precautionary principle to build a working environment safe, healthy and above all, sustainable, and points to the Accident Prevention Factor (APF) as a regulatory tool for the sustainability of the work environment. The research has qualitative and exploratory nature, and used as data collection techniques the direct observation and semistructured interviews to identify the perception of six observers of labor relations about the APF. Moreover, the research was developed with a methodological sequence divided into three phases: preliminary phase - "state of the art", which analyzed the theoretical and bibliographic, which motivated the research field, called "phase of data collection" and "Analytical-conclusive phase" that was a discussion and analysis of data collected. The research is endowed with a methodological basis that allowed portray the factual context of the environment of work and Accident Prevention Factor under the gaze of the Ministry of Labor and Employment, Labour Prosecutor, Social Security, Labour Justice, representing the class of employees and representative of the class of employers.
A pesquisa aborda as percepções do Fator Acidentário de Prevenção como instrumento normativo para o alcance da sustentabilidade no meio ambiente do trabalho. Buscar a sustentabilidade no plano das relações de trabalho conduz à garantia de um ambiente laboral digno às presentes e futuras gerações de trabalhadores. Diante disso, a pesquisa atinge seus objetivos ao expor uma análise histórico-sociológica da transição do trabalho como formação biológico-evolutiva do ser humano à necessidade biológico-social pelo trabalho, abordando o meio ambiente do trabalho e as significativas transformações dos processos produtivos. Outrossim, a pesquisa demonstra a relevância do princípio da precaução para a construção de um meio ambiente do trabalho seguro, saudável e, sobretudo, sustentável, bem como aponta o Fator Acidentário de Prevenção (FAP) como instrumento normativo para a sustentabilidade do ambiente laboral. A pesquisa tem natureza qualitativo-exploratória, tendo utilizado como técnicas de coleta de dados a observação direta e a entrevista semiestruturada para identificar a percepção de seis observadores das relações de trabalho em relação ao FAP. Além disso, a pesquisa desenvolveu-se com uma sequência metodológica dividida em três fases: fase preliminar estado da arte , onde foram analisados os referenciais teóricobibliográficos, que fundamentaram a pesquisa de campo, denominada fase de coleta de dados , e a fase analítico-conclusiva , onde ocorreu a análise e discussão dos dados coletados. A pesquisa é dotada de embasamento metodológico que permitiu retratar o contexto fático do meio ambiente do trabalho e do Fator Acidentário de Prevenção sob o olhar do Ministério do Trabalho e Emprego, Ministério Público do Trabalho, INSS, Justiça do Trabalho, representante da classe dos empregados e representante da classe dos empregadores.
Keywords: Direito; Fator Acidentário de Prevenção; Meio ambiente do trabalho; Princípio da precaução; Sustentabilidade; Pós-modernidade; Ambiente de trabalho; Segurança do trabalho; Segurança do trabalho - Legislação; Direito do trabalho; Accident Prevention Factor; Working environment; Precautionary principle; Sustainability; Postmodernity; Work environment; Industrial safety; Industrial safety - Law and legislation; Labor laws and legislation